2012
DOI: 10.1002/lsm.22034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of infrared laser light‐induced ablation at different wavelengths on bovine intervertebral disc ex vivo: Evaluation with magnetic resonance imaging and histology

Abstract: The 1,470-nm laser light had an effect in the whole nucleus pulposus and not only at the site of the quartz fiber, whereas with the 980-nm laser irradiation, significant changes were demonstrated only at the application site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
7
0
2
Order By: Relevance
“…In another case report, a patient developed a subacute cauda equina syndrome after percutaneous lumbar laser disc decompression (228). In a 2012 publication by Cselik et al (147), the impact of infrared laser light-induced ablation at different wavelengths on bovine intervertebral discs ex vivo was evaluated by MRI and histology. They concluded that the 1470-nm laser light had an effect through the entire nucleus pulposus and not only at the site of the quartz fiber, whereas with the 980-nm laser irradiation, significant changes were demonstrated only at the application site.…”
Section: Wwwpainphysicianjournalcommentioning
confidence: 99%
“…In another case report, a patient developed a subacute cauda equina syndrome after percutaneous lumbar laser disc decompression (228). In a 2012 publication by Cselik et al (147), the impact of infrared laser light-induced ablation at different wavelengths on bovine intervertebral discs ex vivo was evaluated by MRI and histology. They concluded that the 1470-nm laser light had an effect through the entire nucleus pulposus and not only at the site of the quartz fiber, whereas with the 980-nm laser irradiation, significant changes were demonstrated only at the application site.…”
Section: Wwwpainphysicianjournalcommentioning
confidence: 99%
“…Besides the ability to directly visualize the compressive pathology rather than only relying on preoperative imaging and intraoperative fluoroscopy typical of percutaneous laser disc decompression (PLDD), the endoscopic approach affords the surgeon the ability to tailor the operation based on the visualized pathology by addressing more complex structural problems of the diseased motion segment. While PLDD is limited to the shrinkage of the intervertebral disc tissue either via direct thermal or vaporization effects [11][12][13] dictated by the type of laser technology chosen for the operation, the use of power burrs, drills, and advanced cutting rongeurs during a percutaneous endoscopic disc decompression (PEDD) allows bony resection which is often required to achieve adequate decompression in patients with advanced degenerative cervical spine disease. This seemingly trivial and obvious distinction creates the discussion on which procedure best suits what type of cervical disc herniation.…”
Section: Introductionmentioning
confidence: 99%
“…Although IVDD often occurs simultaneously along the entire vertebral column, the discs do not undergo the same levels of degenerative changes at the time for prophylactic treatment. Currently, PLDA of dogs or percutaneous laser disc decompression in humans is performed on the most common sites of thoracolumbar IVDD, and with the same laser fluence applied to each thoracolumbar disc regardless of the differences in the degenerative condition among the discs. It is recognizable that adapting the laser fluence based on the extent of the mineralization of the disc will likely improve the outcomes of PLDA by minimizing under‐ or over‐ablation; however, disc‐specific PLDA procedure is not advocated, at least in dogs, due largely to the limit that the diagnostic imaging has in determining the degenerative extent of the disc in the clinical work‐flow of PLDA.…”
Section: Introductionmentioning
confidence: 99%